Perancangan Sistem Persediaan Stok Obat Pada Apotek Keluarga Jaya Berbasis Web - Martono Martono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Keluarga Jaya Pharmacy is a shop that provides various types of medicines and medical devices where the transaction process is still done traditionally, recording the stock of medicines and medical devices also still uses excel files. Of course, because of this, the transaction process to recording the stock of goods becomes longer and less accurate. Inaccurate and incomplete data on medicines and medical devices often causes medicines that are approaching their expiration date not to be detected as soon as possible. Therefore, the author decided to build a web-based drug stock inventory application at the Keluarga Jaya pharmacy. This system will be able to solve the problems that are currently still being experienced at the Keluaga Jaya pharmacy. The drug stock inventory system that the author built in this study is modeled into a class diagram and also a use case diagram. The results of the study are a web-based drug stock recording system at the Keluarga Jaya pharmacy that has features for logging in, managing master data, managing sales, managing returns, managing reports and logging out.